Evaluation of the Notification Oriented Paradigm Applied to Real-Time Systems - Linhares, Robson Ribeiro; Renaux, Douglas Paulo Bertrand; Simão, Jean Marcelo; Stadzisz, Paulo Cézar (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC), 2014)
Software development based upon current paradigms, such as the Imperative Paradigm (IP) and the Declarative Paradigm (DP), often presents drawbacks such as waste of processing capacity and coupling among entities. This is due to their orientation to a monolithic inference mechanism that is based on causal evaluation implemented by means of searches over passive computational entities. The Notification-Oriented Paradigm (NOP) was conceived as a new approach for conception, structuring, and execution of software leading to performance improvements, organization of causal knowledge, and decoupling of programming entities. The NOP introduces a different manner of structuring software and realization of its inferences, which are based upon small, smart, and decoupled collaborative entities that interact by means of precise notifications. In this way, NOP achieves responsiveness, distributiveness, consistency, and robustness. These features are among the demands of Real-Time Systems. This paper analyzes the NOP applicability to Real-Time Systems by confronting the demands of the latter with the characteristics of the former. As conclusion, the NOP is considered applicable to this sort of computational system.